Termite fauna of sg. Rawog conservation area - Homathevi Rahman; H.M. Chin; Azrul (Sabah Forestry Department, 2019)
This paper presents a preliminary list of termite species collected from Sg. Rawog Conservation Area. Termites were manually collected using standardized 100 m x 2 m belt transect, single transect, at all selected trails. A total of 14 species of termite, belonging to 10 genera of two families (Rhinotermitidae and Termitidae) were recorded within the forests sites of Sg. Rawog. The termite assemblage was dominated by the family Termitidae, comprising of wood-dwelling termites. The termite diversity is lower compared to any other primary forest and all species are commonly found in typical Malaysian forests.